Value of Care: An Exploratory Qualitative Study with Doctors and Patients - Leda Marino; Vincenza Capone (MDPI AG, 2023)
The concept of value in healthcare is mainly based on economic and financial aspects. However, the literature has emphasised the need to investigate value from other perspectives. The present study aimed to explore the views of physicians and patients on the value of healthcare, and to examine in depth the psychosocial and organisational elements that have emerged but that need to be investigated more. Therefore, two qualitative studies were performed, in which 69 physicians and 111 patients participated. The data were analysed using content analysis and text mining using t-lab software. The results revealed common elements between the two healthcare actors that constitute value in healthcare, including competence, professionalism, and soft skills like communication and empathy. Furthermore, the importance of functioning health services and effective organisational culture in local healthcare and investment emerged. These findings can guide healthcare organisations to consider the potential psychosocial factors related to value in healthcare, which affect organisation in terms of costs and healthcare relationships. In addition, these findings are a first step in filling the gap found in the literature regarding the consideration of value from a non-economic perspective and the difficulty of defining and measuring it.